By students, for students - Mercer, Theresa G. (Nature, 2017)
Loneliness, writers' block and demotivation are just three of many challenges faced by PhD students across all disciplines. It was this realization that inspired me and a social-science colleague to organize an event about the experience of being a PhD student.